Biosafety evaluation of BaSi2O2N2:Eu2+/PDMS composite elastomers - Zhang, Zheyuan; Zong, Mingrui; Liu, Jinrong; Ren, Jianing; Liu, Xiaoming; Zhang, Ran; Cui, Jiayu; Sun, Lingxiang; Song, Hao; Zhang, Yanjie; Li, Bing; Wu, Xiuping (Frontiers in Bioengineering and Biotechnology, 2023)
In recent years, mechanoluminescent (ML) materials have shown great potential in stress sensing, mechanical energy collection and conversion, so they have attracted wide attention in the field of stomatology. In the early stage of this study, BaSi2O2N2:Eu 2+ ML phosphors were synthesized by two-step high temperature solid state method, and then mixed with Polydimethylsiloxane (PDMS) in different proportions to obtain BaSi2O2N2:Eu 2+ /PDMS ML composites with different mass fractions (10%,20%,30%,40%,50%). Then its biosafety was evaluated by Cell Counting Kit-8 (CCK-8), Calcein-AM/PI fluorescence staining, hemolysis, oral mucosal irritation, acute and subacute systemic toxicity tests. The experimental results show that the biosafety of BaSi2O2N2:Eu 2+ /PDMS ML composite elastomers with different mass fraction is in line with the existing standards, and other related properties can be further studied.